The Effects of Preparation Period on Motor Skills of Wheelchair Basketball Players: A Pilot Study - Goran Kozomara; Petar Petrovic; Goran Nikolic; Bojan Jorgic; Miodrag Kocic; Marko Aleksandrovic (Journal of Anthropology of Sport and Physical Education, 2019)
The aim of this research is the determination of the preparation period effects on motor skills of wheelchair basketball players. The sample of six wheelchair basketball players in Serbia, aged 20 to 47, with at least five years of sports experience at the national level. The following tests of motor skills were carried out: Maximal pass, Hand dynamometry (for both hands), 5 m sprint test, 20 m sprint test, 5 m sprint with the ball, 20m sprint with the ball, Slalom without a ball and Slam with a ball. To determine the difference in the motor skills tests between the initial and the final measurement, the Student’s t-test for small dependent samples was used. Experimental treatment includes the preparation period of the Serbian national team in wheelchair basketball in the C Division European Championship. An experimental treatment of 15 days duration containing 20 training sessions (2 h duration each) was insufficient for the statistically significant transformation motor skills of wheelchair basketball players. Missing of this research is the small number of examinees and the inhomogeneity of the examined sample. Future studies should estimate the impact of similar training on the motor skills of wheelchair basketball players, on a larger sample and in the function of injuries, impairment and functional classes of players.